Improved Thyroid Hypoechogenicity Following Bariatric-Induced Weight Loss in Euthyroid Adults With Severe Obesity—a Pilot Study - Kyrou, Ioannis; Adesanya, Olu; Hedley, Nicholas; Wayte, Sarah; Grammatopoulos, Dimitris; Thomas, Claire L.; Weedall, Andrew; Sivaraman, Subash; Pelluri, Lavanya; Barber, Thomas M.; Menon, Vinod; Randeva, Harpal S.; et al. (Frontiers in Endocrinology, 2018)
Background: Obesity may affect both biochemical thyroid function tests; and thyroid morphology, as assessed using ultrasound scans (US). The aim of the present pilot study was to explore whether weight loss achieved by bariatric surgery alters thyroid US morphology including grey-scale measurements; and/or function in euthyroid adults with severe obesity. Methods: Euthyroid adults (>18 years) with body mass index (BMI) ≥40 kg/m2 and negative thyroid peroxidase antibodies were assessed at baseline (pre-surgery) and after achieving at least 5% weight loss of their baseline body weight following bariatric surgery. Anthropometric assessments, biochemical/hormonal measurements (TSH, free-T4, free-T3, reverse-T3 and leptin) and thyroid US with grey-scale histogram analysis were performed at the baseline and post-surgery follow-up. Results: Ten Caucasian, euthyroid patients (women/men: 8/2; age: 48.6±3.1 years; BMI: 51.4±1.8 kg/m2) successfully completed this study with significantly decreased body weight (>5% weight loss), waist circumference and serum leptin levels post-surgery (mean post-surgery follow-up duration: 16.5±2.5 months). In parallel to the observed bariatric-induced weight loss, thyroid US echogenicity increased by 25% (p=0.03), without significant changes in thyroid volume. No significant changes in thyroid function tests were detected. No significant correlations were observed between the increase in thyroid echogenicity and the decreases in anthropometric parameters and circulating leptin. Conclusion: Our results indicate that in euthyroid adults with severe obesity, marked weight loss achieved by bariatric surgery is associated with a parallel significant increase in the thyroid US echogenicity, suggesting that morphological changes of the thyroid in obesity are reversible with weight loss. ClinicalTrials.gov Identifier: NCT03048708